Transcriptional Pattern of Genes Coding for the Proteolytic System of Lactococcus lactis and Evidence for Coordinated Regulation of Key Enzymes by Peptide Supply - Guédon, Eric (American Society for Microbiology, 2001)
The transcription of 16 genes encoding 12 peptidases (pepC, pepN, pepX, pepP, pepA, pepF2, pepDA1, pepDA2, pepQ, pepT, pepM, and pepO1), P(I) and P(III) proteinases (prtP1 and prtP3), and three transport systems (dtpT, dtpP, and opp-pepO1) of Lactococcus lactis MG1363 was analyzed in response to different environmental factors. Promoter fusions with luciferase reporter genes and/or mRNA analysis were used to study the effects of sugar sources, growth at 37°C, and peptide supply on the transcription of these genes. Only transcription of the pepP gene is modulated by the source of sugar. The presence of potential catabolite-responsive element (CRE) boxes in its promoter region suggests that expression of this gene is directly controlled by catabolic repression. Elevated temperature had no significant effect on the level of transcription of these genes. prtP1, prtP3, pepC, pepN, pepX, and the opp-pepO1 operon are the most highly expressed genes in chemically defined medium, and their expression is repressed 5- to 150-fold by addition of peptide sources such as Casitone in the medium. Moreover, the transcription of prtP1, prtP3, pepC, pepN, and the opp-pepO1 operon is repressed two- to eight-fold by the dipeptides leucylproline and prolylleucine. The transcription of pepDA2 might also be repressed by the peptide sources, but this effect is not observed on the regulation of dtpT, pepP, pepA, pepF2, pepDA1, pepQ, pepT, pepM, and the dtpP operon. The significance of these results with respect to the functions of different components of the proteolytic system in L. lactis are discussed.